2018
DOI: 10.2134/jeq2017.08.0329
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Soil Organic Carbon Distribution in Central Chile under Future Climate Scenarios

Abstract: Soil organic C (SOC) is the largest terrestrial C pool, and it influences diverse soil properties and processes in a landscape. At global scales, SOC is related to climate; as climate changes, we expect that SOC will change at broad scales as well, but how SOC will respond to climate change in diverse environments is complex and highly uncertain. To evaluate the potential impact of predicted changes in temperature and precipitation across central Chile, we first estimated current SOC content using pedon descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This study focuses on Latin America, where site-or region-specific modeling efforts report high explained variance when mapping SOC (Reyes-Rojas et al, 2018). Accurate SOC maps are required to identify areas with the potential for soil carbon sequestration, and distinguish them from areas with high SOC.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on Latin America, where site-or region-specific modeling efforts report high explained variance when mapping SOC (Reyes-Rojas et al, 2018). Accurate SOC maps are required to identify areas with the potential for soil carbon sequestration, and distinguish them from areas with high SOC.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made to assess the response of SOC stocks in topsoil to warming (Davidson and Janssens, 2006; Conant et al, 2011; Crowther et al, 2016). Most SOC measurements were limited to the top 10‐ to 30‐cm depths, and few papers accounted for subsoil SOC stocks (Cavigelli et al, 2018; Dell et al, 2018; Gollany and Polumsky, 2018; Reyes Rojas et al, 2018). Findings from these studies identified critical gaps in knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Four papers in the section (summarized below) applied statistical models to develop maps of current SOC stocks across different geographical regions and spatial scales, including a 15‐km 2 area in southeastern Brazil (Costa et al, 2018), two different 100‐km 2 regions in South Africa (Vågen et al, 2018), a 100,000‐km 2 region of the northwestern United States (Flathers and Gessler, 2018), and a 150,000‐km 2 region in central Chile (Reyes Rojas et al, 2018). Two of these efforts (Flathers and Gessler, 2018; Reyes Rojas et al, 2018) used random forest statistics with the scorpan modeling approach of McBratney et al (2003), which uses seven categories of input data to make SOC predictions: known soil attributes, climatic values, organisms present, relief, parent material, age, and spatial location. In addition to assessing current SOC stocks, Reyes Rojas et al (2018) extended their effort to assessing future climate effects.…”
Section: Statistical Models To Assess Soil Organic Carbon Stocksmentioning
confidence: 99%
See 2 more Smart Citations